Diseases of Fruits and Vegetables: Volume II
DOI: 10.1007/1-4020-2607-2_1
|View full text |Cite
|
Sign up to set email alerts
|

Avocado Diseases of Major Importance Worldwide and their Management

Abstract: Avocado fruit has become one of the most sought after food sources worldwide. It is a nutritious source of food and is part of the staple diet of many people in third world countries where it is cultivated and where it is native. Avocado is a specialty fruit, produced on a large scale in more than 30 countries around the world and because of its appeal, it is an industry that continues to grow. It is a very lucrative industry, and with over production growers have been forced to develop overseas markets, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Quiescent infections can occur in fruits and leaves. The fungus infects young fruits but enters a dormant phase until fruit maturity (Marais, 2004). Confusion with other pathogens/pests Dothiorella aromatica (Sacc) Petr & Syd.…”
Section: Presence Of Asymptomatic Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quiescent infections can occur in fruits and leaves. The fungus infects young fruits but enters a dormant phase until fruit maturity (Marais, 2004). Confusion with other pathogens/pests Dothiorella aromatica (Sacc) Petr & Syd.…”
Section: Presence Of Asymptomatic Plantsmentioning
confidence: 99%
“…• Infected nursery stock, contaminated soil/substrate and fruits are the main pathways (PRA by the Australian Government). • The pathogen can be dispersed through spores on dead twigs, leaves and mummified fruit (Marais, 2004). • Rain and humidity facilitate the spore production and dispersal (Marais, 2004).…”
Section: Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…6 It is worth mentioning that although some CAMR genotypes are susceptible to damage caused by insects (e.g., Trioza anceps, Heilipus lauri, and Thysanoptera: Thripidae) and pathogenic fungi (e.g., Phytophthora cinnamomi, Colletotrichum gloeosporioides, and Sphaceloma perseae) that cause damage to avocado crops, the damage is less than in commercial varieties such as'Hass' and 'Fuerte'. 7 In addition, there are resistant genotypes, Sánchez-Gonzales et al 8 reported the resistance of CAMR rootstocks to Phytophthora cinnamomi; main pathogen that affect avocado production worldwide, causing root rot and secondary symptoms in the upper part of the plant, including dieback of branches, yellowing and wilting leaves, complete defoliation and death of the tree.…”
Section: Introductionmentioning
confidence: 99%
“…and crown canker of avocado. After P. cinnamomi , and this pathogen has been recorded in almost 90% of the avocado orchards in California ( Coffey, 1987 ; Marais, 2004 ). Furthermore, P. citricola has been reported as the second most destructive causal agent of root rot ( Schubert et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%